Supervisi Klinis: Peningkatan Kemampuan Guru dalam Mengajar di Wilayah MI Binaan Kecamatan Semin Gunungkidul Semester I Tahun 2016/2017 - Karmanto Karmanto (Jurnal Pendidikan Madrasah, 2018)
AbstractClinical supervision is one form of supervision focused on improving teaching through cycles. The technique is done by individual and group methods. The method of implementation is by methods such as Focused Group Discussion (FGD) and observation. Implementation of supervision is carried out in one semester in accordance with the material that has been scheduled, among others, carrying out guidance and guidance of teachers and / or the head of the madrasa. The results of actions that increased in the second cycle, the average ability of teachers to teach in accordance with the standard process, especially in teaching performance has met the criteria of success that is good. In the first cycle there were 50% or half of the 6 teachers who did not meet the criteria either, 2 teachers or 33.33% with good criteria and 1 teacher or 16.67% very good. Or the average value of the first cycle of 79.85 increased in the second cycle to 84.30 or increased to 4.44%. After being given action on the second stage of the teacher's teaching ability to be 100%, one of them with very good criteria with a value of 94.22 or 16.67%. Keywords: Clinical Supervision Techniques, Increasing Teacher’s Ability to Teach AbstrakHasil penelitian menunjukkan bahwa supervisi klinis adalah salah satu bentuk supervisi yang difokuskan pada peningkatan mengajar melalui siklus. Adapun teknisnya dilakukan dengan cara individual dan kelompok. Metode pelaksanaannnya adalah dengan metode antara lain FGD (Focused Group Discussion) dan observasi Pelaksanaan supervisi dilakukan dalam satu semester sesuai dengan materi yang telah diagendakan, antara lain melaksanakan pembimbingan dan pembinaan guru dan/atau kepala madrasah. Hasil tindakan yang meningkat pada siklus II, rata-rata kemampuan guru mengajar sesuai dengan standar proses terutama dalam penampilan mengajar sudah memenuhi kriteria keberhasilan yaitu baik. Pada siklus I terdapat 50% atau setengah dari jumlah 6 guru belum memenuhi kriteria baik, 2 guru atau 33,33% dengan kriteria baik serta 1 guru atau 16,67% sangat baik. Atau nilai rata-rata siklus I 79,85 meningkat pada siklus II menjadi 84,30 atau naik menjadi 4,44%. Setelah diberi tindakan pada siklus II kemampuan guru mengajar menjadi 100%, satu diantaranya dengan kriteria sangat baik dengan nilai 94,22 atau 16,67%. Kata Kunci: Teknik Supervisi Klinis, Peningkatan Kemampuan Guru dalam Mengajar